The future of global mobility - Mello, Rodrigo; Suutari, Vesa; Escobar-Borruel, Inés; Biswas, Tania S.; Dickmann, Michael (HENRY (Finland), 2021)
This article presents different kinds of international work featured in the literature, and a number of new strategic trends following the COVID-19 pandemic, identified in recent interviews with the heads of global mobility units in 22 European companies. Given our findings, which describe the extensive impacts of the crisis on global mobility, we make two main recommendations for MNCs: (1) they need to reconsider global mobility policies in a new situation after the COVID pandemic; and (2) invest in overcoming operational and legal challenges, to reduce uncertainties among globally mobile employees surrounding the use of flexible and remote working arrangements.
Keywords: Global mobility policy; COVID-19; expatriate; long-term assignment; short-term assignment; international business traveler; virtual assignment